The effects of infrastructure expenditure to the Economic Growth of Central Luzon (1998-2008) - Capili, Crysler Delos Santos; Macaraeg, Adrian; Romero, Jan Miguel Miranda; Roque, Jerson Agamilla; Yap, Virginia C. (Pampanga University of the Philippines Diliman Extension Program in Pampanga, 2010)
This study presents an analysis of the contribution of infrastructure expenditures, specifically on transport infrastructures, to the economic growth of Central Luzon for the period 1998-2008. This study determines whether or not such expenditures have indeed contributed to the region's investment, employment, and economic growth. Specifically, this paper helps identify if expenditures in transportation infrastructures is really crucial in propelling regional economic growth, and thus help policy makers channel scarce resources to their most efficient and effective uses.

This paper is a correlation study which seeks relationship between Infrastructure expenditure and the related variables, namely Gross Regional Domestic Product, Employment, and Investment. Secondary data, gathered from different government agencies, are used to support the study.

The findings showed that infrastructure expenditure has a significant relationship with Gross Regional Domestic Product of Central Luzon. Infrastructure expenditure also affects consumption, level of employment, and the level of investment in Central Luzon positively. The researchers, thus, recommend that the government should allocate more resources to this kind of resource allocation, and to conduct further studies about the effect of infrastructures to the economic growth of a country.
Thesis (Business Economics) UPDEPP, c2025.
Keywords: Infrastructure (Economics) -- Government policy -- Philippines -- Central Luzon; Public works -- Economic aspects -- Philippines -- Central Luzon; Economic development -- Philippines -- Central Luzon